Transcendentality, Perceptivity, and Existential Ontology - Pivorius, Vytautas (Problemos, 1994)
The ontological conceptions of M. Heidegger and M. Merleau-Ponty are discussed in the paper. The preconditions of the possibilities of human understanding are shown to be discovered making the transcendental method more radical.